Aqueous phase synthesis method and application of hierarchical pore metal organic framework material ZIF-8

Through the aqueous phase synthesis method of the multi-stage pore metal organic framework material ZIF-8, the problem of restricting adsorption performance of the existing MOFs microporous structure is solved, and a multi-stage pore ZIF-8 material with high efficiency adsorption performance was prepared for environmental removal. The diclofenac sodium, flunicin megluamine and meloxicam in it achieve an increase in adsorption capacity and rate, and supports the regeneration and recycling of materials.

CN119241856APending Publication Date: 2025-01-03HENAN NORMAL UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411324006.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The microporous structure of existing MOFs limits the diffusion rate of the target molecules and hinders the entry of macromolecules into the active sites of MOFs, resulting in insufficient adsorption performance and it is difficult to effectively remove diclofenac sodium, flunicin megluamine and meloxicon in the environment. .

Method used

Using the aqueous phase synthesis method of multi-stage pore metal organic framework material ZIF-8, zinc nitrate hexahydrate and surfactant were stirred at a specific molar ratio, dimethylimidazole was added, and then eluted and dried after reaction. ZIF-8 material with microporous and mesoporous structures for adsorption and removal of target drugs.

Benefits of technology

The prepared multi-stage pore ZIF-8 material combines the high specific surface area of ​​the microporous structure and the pore size of the mesoporous structure, significantly improving the adsorption capacity and rate, and adsorption performance of diclofenac sodium, flunicin megluamine and meloxicam , and the adsorption process is simple, and the solid and liquid are easy to separate and recycle.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241856A_ABST
    Figure CN119241856A_ABST
Patent Text Reader

Abstract

The invention discloses a water-phase synthesis method and application of a hierarchical pore metal organic framework material ZIF-8, and the specific preparation process is as follows: dissolving zinc nitrate hexahydrate in deionized water, stirring at 20-40 DEG C for 5-10 min, then adding a surfactant as a soft template until the surfactant is completely dissolved to obtain a solution A; dimethylimidazole is dissolved in deionized water, and a solution B is obtained; and uniformly mixing the solution A and the solution B, reacting at 20-40 DEG C for 2-6 hours, eluting and drying to obtain the hierarchical pore metal organic framework material ZIF-8. The hierarchical pore metal organic framework material prepared by the invention has strong capability of simultaneously adsorbing target molecules of diclofenac sodium, flunixin meglumine and meloxicam in an aqueous solution and high adsorption capacity, and can be used for adsorbing and removing the target molecules of diclofenac sodium, flunixin meglumine and meloxicam in an actual environmental sample.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of hierarchical porous metal organic framework materials and adsorption treatment of diclofenac sodium, flunixin meglumine and meloxicam in environmental samples, and specifically relates to an aqueous phase synthesis method and application of a hierarchical porous metal organic framework material ZIF-8. Background Art

[0002] Diclofenac sodium, flunixin meglumine and meloxicam are common nonsteroidal anti-inflammatory drugs, which are widely used to treat symptoms such as pain, inflammation and fever. However, due to the extensive use of these drugs, their residues in the environment pose a potential risk to the ecosystem and human health. It is difficult for wastewater treatment systems to completely remove these drug residues, causing them to enter the natural environment such as water bodies and soil, which may have toxic effects on aquatic organisms and accumulate through the food chain, ultimately affecting human health. Therefore, it is necessary to develop adsorption and removal methods for these drugs to reduce their residues in the environment and protect the balance of the ecosystem and the health of the public.

[0003] Metal-organic frameworks (MOFs) have become ideal adsorption materials due to their unique physicochemical properties, such as high specific surface area, abundant coordination unsaturated sites, high chemical stability, and highly active atoms and functional groups. The size and shape of the internal pores of MOFs are one of the key factors that determine their adsorption performance. Substances need to pass through these pores to reach the internal active sites in order to undergo adsorption reactions. However, the pore structure of most MOFs is currently microporous (pore size less than 2nm), which to a certain extent limits the diffusion rate of target molecules and also hinders the entry of macromolecules into the internal active sites of MOFs. Therefore, it is particularly important to develop an effective and reliable strategy to transform microporous MOFs into hierarchical MOFs with mesoporous structures. In this hierarchical porous material, the microporous structure provides adsorption capacity, while the mesoporous structure accelerates the diffusion and transport of guest molecules. By introducing the mesoporous structure, the adsorption capacity and rate of MOFs are improved, thereby expanding their application areas. Summary of the invention

[0004] The technical problem solved by the present invention is to provide an aqueous phase synthesis method of a hierarchical porous metal-organic framework material ZIF-8. The hierarchical porous metal-organic framework material ZIF-8 prepared by the method has good adsorption performance for target molecules diclofenac sodium, flunixin meglumine and meloxicam, and can be used for the adsorption and removal of diclofenac sodium, flunixin meglumine and meloxicam in actual environmental samples.

[0005] The present invention adopts the following technical scheme to solve the above technical problems. The invention is an aqueous phase synthesis method of a multi-level porous metal organic framework material ZIF-8, which is characterized by the specific process of: dissolving zinc nitrate hexahydrate in deionized water, stirring at 20-40°C for 5-10 minutes, adding a surfactant as a soft template until it is completely dissolved to obtain a solution A, wherein the soft template is one or more of dodecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide or octadecyltrimethylammonium bromide; dissolving dimethylimidazole in deionized water to obtain a solution B; mixing the solution A and the solution B evenly, reacting at 20-40°C for 2-6 hours, and then eluting and drying to obtain the multi-level porous metal organic framework material ZIF-8.

[0006] It is further defined that the molar ratio of the soft template to zinc nitrate hexahydrate is 1:0.1-1.5.

[0007] It is further defined that the molar ratio of the soft template to zinc nitrate hexahydrate is 1:1.

[0008] It is further defined that the elution process is used to remove the soft template in the reaction system, and the specific process is: washing with deionized water 2 to 4 times.

[0009] The aqueous phase synthesis method of the hierarchical porous metal-organic framework material ZIF-8 described in the present invention is characterized by the specific steps of: dissolving 0.733g of zinc nitrate hexahydrate in 50mL of deionized water, adding 0.8980g of soft template surfactant hexadecyltrimethylammonium bromide and completely dissolving it to obtain solution A; dissolving 1.622g of dimethylimidazole in 50mL of deionized water to obtain solution B; mixing solution A and solution B evenly, reacting at room temperature for 3h, and then eluting and drying to obtain the hierarchical porous metal-organic framework material ZIF-8.

[0010] The multi-level porous metal organic framework material ZIF-8 of the present invention is used for adsorption and removal of diclofenac sodium, flunixin meglumine or / and meloxicam in actual environmental samples. The specific process is: placing the multi-level porous metal organic framework material ZIF-8 in an actual environmental water sample containing diclofenac sodium, flunixin meglumine or / and meloxicam to achieve adsorption of diclofenac sodium, flunixin meglumine or / and meloxicam, and then using methanol as an elution solvent to achieve enrichment of diclofenac sodium, flunixin meglumine or / and meloxicam and regeneration and recycling of the multi-level porous metal organic framework material ZIF-8.

[0011] Compared with the prior art, the present invention has the following advantages and beneficial effects: 1. The present invention provides an aqueous phase synthesis method and application of a hierarchical porous metal-organic framework material ZIF-8, which can simultaneously and efficiently remove diclofenac sodium, flunixin meglumine and meloxicam from environmental samples.

[0012] 2. The multi-level porous metal organic framework material ZIF-8 prepared by the present invention combines the dual advantages of large specific surface area of ​​microporous structure and large pore size of mesoporous structure, and has excellent properties such as strong affinity and large adsorption capacity. In addition, the adsorption process is simple, and the solid and liquid are easy to separate and regenerate for recycling, which provides a reference for the preparation of new multi-level porous metal organic framework materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 It is the synthesis route of HP-ZIF-8 in the present invention.

[0014] Figure 2 1 and 2 are scanning electron microscope images of ZIF-8 (a) and HP-ZIF-8 (b) in the present invention.

[0015] Figure 3 The N2 adsorption-desorption isotherms (a) and BJH pore size distribution (b) of ZIF-8 and HP-ZIF-8 of the present invention. (Note: (1) acetonitrile (2) acetonitrile / water = 60 / 40 (3) methanol / water = 80 / 20 (4) methanol / water / acetic acid = 80 / 19 / 1 (5) methanol / water / acetic acid = 80 / 18 / 2 (6) methanol.) Figure 4 It is the thermogravimetric analysis diagram of ZIF-8 and HP-ZIF-8 of the present invention.

[0016] Figure 5 It is the adsorption kinetic curve of diclofenac sodium by ZIF-8 and HP-ZIF-8 of the present invention.

[0017] Figure 6 It is the adsorption kinetic curve of flunixin meglumine by ZIF-8 and HP-ZIF-8 of the present invention.

[0018] Figure 7 This is the adsorption kinetic curve of meloxicam by ZIF-8 and HP-ZIF-8 of the present invention. DETAILED DESCRIPTION

[0019] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention. Example 1

[0020] 0.733g (2.5mmol) of zinc nitrate hexahydrate was dissolved in 50mL of deionized water, and then 2.5mmol of soft template surfactant hexadecyltrimethylammonium bromide was added and completely dissolved to obtain solution A; 1.622g (16.8mmol) of dimethylimidazole was dissolved in 50mL of deionized water to obtain solution B; solution A and solution B were mixed evenly and reacted at room temperature for 3h, the obtained powder was filtered out and washed with deionized water 3 times to remove the surfactant. The synthesized sample was rinsed and dried in vacuum at 60℃ to obtain a hierarchical porous metal organic framework material ZIF-8, named HP-ZIF-8, which has uniform particle size and has good adsorption properties for the target analytes diclofenac sodium, flunixin meglumine and meloxicam. Example 2

[0021] 0.733g (2.5mmol) zinc nitrate hexahydrate was dissolved in 50mL deionized water, and then 2.5mmol soft template surfactant dodecyl trimethyl ammonium bromide was added and completely dissolved to obtain solution A; 1.622g (16.8mmol) dimethyl imidazole was dissolved in 50mL deionized water to obtain solution B; solution A and solution B were mixed evenly and reacted at room temperature for 3h, the obtained powder was filtered out and washed with deionized water 3 times to remove the surfactant. The synthesized sample was rinsed and dried in vacuum at 60℃ to obtain a hierarchical porous metal organic framework material ZIF-8, named HP-ZIF-8, which has uniform particle size and has good adsorption properties for the target analytes diclofenac sodium, flunixin meglumine and meloxicam. Example 3

[0022] 0.733g (2.5mmol) zinc nitrate hexahydrate was dissolved in 50mL deionized water, and then 2.5mmol of soft template surfactant tetradecyl trimethyl ammonium bromide was added and completely dissolved to obtain solution A; 1.622g (16.8mmol) dimethyl imidazole was dissolved in 50mL deionized water to obtain solution B; solution A and solution B were mixed evenly and reacted at room temperature for 3h, the obtained powder was filtered out and washed with deionized water 3 times to remove the surfactant. The synthesized sample was rinsed and dried in vacuum at 60℃ to obtain a hierarchical porous metal organic framework material ZIF-8, named HP-ZIF-8, which has uniform particle size and has good adsorption properties for the target analytes diclofenac sodium, flunixin meglumine and meloxicam. Example 4

[0023] 0.733g (2.5mmol) of zinc nitrate hexahydrate was dissolved in 50mL of deionized water, and then 2.5mmol of soft template surfactant octadecyl trimethyl ammonium bromide was added and completely dissolved to obtain solution A; 1.622g (16.8mmol) of dimethyl imidazole was dissolved in 50mL of deionized water to obtain solution B; solution A and solution B were mixed evenly and reacted at room temperature for 3h, the obtained powder was filtered out and washed with deionized water 3 times to remove the surfactant. The synthesized sample was rinsed and dried in vacuum at 60℃ to obtain a hierarchical porous metal organic framework material ZIF-8, named HP-ZIF-8, which has uniform particle size and has good adsorption properties for the target analytes diclofenac sodium, flunixin meglumine and meloxicam. Example 5

[0024] 0.733g (2.5mmol) zinc nitrate hexahydrate was dissolved in 50mL deionized water, and 0.25mmol soft template surfactant hexadecyltrimethylammonium bromide was added and completely dissolved to obtain solution A; 1.622g (16.8mmol) dimethylimidazole was dissolved in 50mL deionized water to obtain solution B; solution A and solution B were mixed evenly and reacted at room temperature for 3h, the obtained powder was filtered out and washed with deionized water 3 times to remove the surfactant. The synthesized sample was rinsed and dried in vacuum at 60℃ to obtain a hierarchical porous metal organic framework material ZIF-8, named HP-ZIF-8, which has uniform particle size and has good adsorption properties for the target analytes diclofenac sodium, flunixin meglumine and meloxicam. Example 6

[0025] 0.733g (2.5mmol) zinc nitrate hexahydrate was dissolved in 50mL deionized water, and then 0.5mmol soft template surfactant hexadecyltrimethylammonium bromide was added and completely dissolved to obtain solution A; 1.622g (16.8mmol) dimethylimidazole was dissolved in 50mL deionized water to obtain solution B; solution A and solution B were mixed evenly and reacted at room temperature for 3h, the obtained powder was filtered out and washed with deionized water 3 times to remove the surfactant. The synthesized sample was rinsed and dried in vacuum at 60℃ to obtain a hierarchical porous metal organic framework material ZIF-8, named HP-ZIF-8, which has uniform particle size and has good adsorption properties for the target analytes diclofenac sodium, flunixin meglumine and meloxicam. Example 7

[0026] 0.733g (2.5mmol) zinc nitrate hexahydrate was dissolved in 50mL deionized water, and 0.75mmol soft template surfactant hexadecyltrimethylammonium bromide was added and completely dissolved to obtain solution A; 1.622g (16.8mmol) dimethylimidazole was dissolved in 50mL deionized water to obtain solution B; solution A and solution B were mixed evenly and reacted at room temperature for 3h, the obtained powder was filtered out and washed with deionized water 3 times to remove the surfactant. The synthesized sample was rinsed and dried in vacuum at 60℃ to obtain a hierarchical porous metal organic framework material ZIF-8, named HP-ZIF-8, which has uniform particle size and has good adsorption properties for the target analytes diclofenac sodium, flunixin meglumine and meloxicam. Example 8

[0027] 0.733g (2.5mmol) zinc nitrate hexahydrate was dissolved in 50mL deionized water, and then 1.25mmol soft template surfactant hexadecyltrimethylammonium bromide was added and completely dissolved to obtain solution A; 1.622g (16.8mmol) dimethylimidazole was dissolved in 50mL deionized water to obtain solution B; solution A and solution B were mixed evenly and reacted at room temperature for 3h, the obtained powder was filtered out and washed with deionized water 3 times to remove the surfactant. The synthesized sample was rinsed and dried in vacuum at 60℃ to obtain a hierarchical porous metal organic framework material ZIF-8, named HP-ZIF-8, which has uniform particle size and has good adsorption properties for the target analytes diclofenac sodium, flunixin meglumine and meloxicam. Example 9

[0028] 0.733g (2.5mmol) zinc nitrate hexahydrate was dissolved in 50mL deionized water, and then 1.5mmol soft template surfactant hexadecyltrimethylammonium bromide was added and completely dissolved to obtain solution A; 1.622g (16.8mmol) dimethylimidazole was dissolved in 50mL deionized water to obtain solution B; solution A and solution B were mixed evenly and reacted at room temperature for 3h, the obtained powder was filtered out and washed with deionized water 3 times to remove the surfactant. The synthesized sample was rinsed and dried in vacuum at 60℃ to obtain a hierarchical porous metal organic framework material ZIF-8, named HP-ZIF-8, which has uniform particle size and has good adsorption properties for the target analytes diclofenac sodium, flunixin meglumine and meloxicam.

[0029] Comparative Example 1 0.733 g (2.5 mmol) of zinc nitrate hexahydrate was dissolved in 50 mL of deionized water to obtain solution A; 1.622 g (16.8 mmol) of dimethylimidazole was dissolved in 50 mL of deionized water to obtain solution B; solution A and solution B were mixed evenly and reacted at room temperature for 3 hours, the obtained powder was filtered out and washed with deionized water 3 times to remove the surfactant. The synthesized sample was rinsed and dried in vacuum at 60 ° C to obtain a metal organic framework material, named ZIF-8.

[0030] The porosity and BET specific surface area of ​​the HP-ZIF-8 material synthesized in Example 1 were analyzed by N2 adsorption-desorption test. The results are as follows: Figure 3 The isotherm of HP-ZIF-8 material is type IV with obvious hysteresis loop, indicating that there are both micropores and mesopores in HP-ZIF-8 material. Figure 3 The corresponding pore size distribution curve shown in (b) can further confirm the formation of mesopores in the synthesized HP-ZIF-8 material.

[0031] The thermal stability of the HP-ZIF-8 material and the conventional ZIF-8 material prepared in Example 1 was analyzed by thermogravimetric analysis. Figure 4 As shown, the thermal stability of HP-ZIF-8 material can reach 600℃, indicating that HP-ZIF-8 material has good thermal stability. Example 10

[0032] 10 mg of HP-ZIF-8 and conventional ZIF-8 prepared in Example 1 were mixed with 10 mL of 20 mg L -1 The mixture was mixed with a diclofenac sodium aqueous solution, and after oscillation and adsorption at room temperature for a certain period of time, the mixture was filtered with a filter membrane with a pore size of 0.22 μm, and then the content of diclofenac sodium in each supernatant was measured. Figure 5 As shown in Figure 2, the adsorption capacity of diclofenac sodium in aqueous solution by HP-ZIF-8 material is 44.03 mg g -1 Under the corresponding conditions, the adsorption capacity of ZIF-8 material was only 10.69 mg g -1 , indicating that HP-ZIF-8 material has good adsorption performance for diclofenac sodium.

[0033] Methanol was used as the desorption solvent, and the eluent was mixed with the adsorbent material and vortexed for 30 minutes. The content of diclofenac sodium in the supernatant was determined and the removal amount was calculated. The HP-ZIF-8 material can be reused 10 times and the removal rate of diclofenac sodium by the HP-ZIF-8 material has no significant decrease and remains at about 80%, indicating that the HP-ZIF-8 material has good regeneration performance and stability. Embodiment 11

[0034] 10 mg of HP-ZIF-8 and conventional ZIF-8 prepared in Example 1 were mixed with 10 mL of 20 mg L -1 The mixture was mixed with a flunixin meglumine aqueous solution, and after oscillation and adsorption at room temperature for a certain period of time, the mixture was filtered with a filter membrane with a pore size of 0.22 μm, and then the content of flunixin meglumine in each supernatant was measured. Figure 6 As shown in Figure 2, the adsorption capacity of diclofenac sodium in aqueous solution by HP-ZIF-8 material is 41.07 mg g -1 Under the corresponding conditions, the adsorption capacity of ZIF-8 material was only 9.83 mg g -1 , indicating that HP-ZIF-8 material has good adsorption performance for flunixin meglumine.

[0035] Methanol was used as the desorption solvent, and the eluent was mixed with the adsorbent material and vortexed for 30 minutes. The content of flunixin meglumine in the supernatant was determined and the removal amount was calculated. The HP-ZIF-8 material can be reused 10 times and the removal rate of flunixin meglumine by the HP-ZIF-8 material has no significant decrease and remains at about 80%, indicating that the HP-ZIF-8 material has good regeneration performance and stability. Example 12

[0036] 10 mg of HP-ZIF-8 and conventional ZIF-8 prepared in Example 1 were mixed with 10 mL of 20 mg L -1 The mixture was mixed with a meloxicam aqueous solution and adsorbed at room temperature for a certain period of time under oscillation, and then filtered with a filter membrane with a pore size of 0.22 μm, and then the meloxicam content in each supernatant was measured. Figure 7 As shown in Figure 2, the adsorption capacity of diclofenac sodium in aqueous solution by HP-ZIF-8 material is 35.17 mg g -1 Under the corresponding conditions, the adsorption capacity of ZIF-8 material was only 5.54 mg g -1 , indicating that HP-ZIF-8 material has good adsorption performance for meloxicam.

[0037] Methanol was used as the desorption solvent, and the eluent was mixed with the adsorbent material and vortexed for 30 minutes. The meloxicam content in the supernatant was determined and the removal amount was calculated. The HP-ZIF-8 material can be reused 10 times and the removal rate of meloxicam by the HP-ZIF-8 material has no significant decrease and remains at about 80%, indicating that the HP-ZIF-8 material has good regeneration performance and stability.

[0038] The above embodiments describe the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for illustrating the principles of the present invention. Without departing from the scope of the principles of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of protection of the present invention.

Claims

1. A method for aqueous synthesis of a hierarchically porous metal organic framework material ZIF-8, characterized in that The specific process is as follows: dissolve zinc nitrate hexahydrate in deionized water, stir at 20-40°C for 5-10 minutes, add a surfactant as a soft template until it is completely dissolved to obtain solution A, wherein the soft template is one or more of dodecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide or octadecyltrimethylammonium bromide; dissolve dimethylimidazole in deionized water to obtain solution B; mix solution A and solution B evenly, react at 20-40°C for 2-6 hours, and then wash and dry to obtain a hierarchical porous metal-organic framework material ZIF-8.

2. The aqueous phase synthesis method of the multi-level porous metal organic framework material ZIF-8 according to claim 1, characterized in that: The molar ratio of the soft template to zinc nitrate hexahydrate is 1:0.1-1.

5.

3. The aqueous phase synthesis method of the multi-level porous metal organic framework material ZIF-8 according to claim 1, characterized in that: The molar ratio of the soft template to zinc nitrate hexahydrate is 1:

1.

4. The aqueous phase synthesis method of the multi-level porous metal organic framework material ZIF-8 according to claim 1, characterized in that: The elution process is used to remove the soft template in the reaction system, and the specific process is: washing with deionized water 2 to 4 times.

5. The aqueous phase synthesis method of the multi-level porous metal organic framework material ZIF-8 according to claim 1, characterized in that The specific steps are as follows: dissolve 0.733 g zinc nitrate hexahydrate in 50 mL deionized water, then add 0.8980 g soft template surfactant hexadecyltrimethylammonium bromide and completely dissolve it to obtain solution A; dissolve 1.622 g dimethylimidazole in 50 mL deionized water to obtain solution B; mix solution A and solution B evenly, react at room temperature for 3 hours, and then wash and dry to obtain a hierarchical porous metal-organic framework material ZIF-8.

6. The multi-level porous metal organic framework material ZIF-8 prepared by the method according to any one of claims 1 to 5 is used for the adsorption and removal of diclofenac sodium, flunixin meglumine and / or meloxicam in actual environmental samples, characterized in that The specific process is: placing the hierarchical porous metal-organic framework material ZIF-8 in an actual environmental water sample containing diclofenac sodium, flunixin meglumine and / or meloxicam to achieve the adsorption of diclofenac sodium, flunixin meglumine and / or meloxicam, and then using methanol as the elution solvent to achieve the enrichment of diclofenac sodium, flunixin meglumine and / or meloxicam and the regeneration and recycling of the hierarchical porous metal-organic framework material ZIF-8.

Citation Information

Cited By

  • Preparation method of zinc-based metal organic framework fluorescent probe and application of zinc-based metal organic framework fluorescent probe in water environment detection

    CN122404729A